Some positive effects of pine oil on brain tissue in streptozotocin-induced diabetic rats - Demir, Ersin; Keser, Serhat; Yilmaz, Ökkes (Chemical Society of Pakistan, 2016)
Pine oil has antiseptic, expectorant and antioxidant properties and has been used for treatment of rheumatism, respiratory and urinary system and skin diseases. We aimed to determine protective effects of pine oil (PO) on the lipid-soluble vitamins, cholesterol, GSH, total protein, MDA, fatty acid levels of brain tissue of the streptozotocin-induced diabetic rats. Rats were randomly divided into three groups: Control (C), streptozotocin (STZ), streptozotocin+pine oil (PO) groups. Streptozotocin was injected intraperitoneally single dose (65 mg/kg) to the STZ and PO groups for inducing of diabetes. To the PO group 1 mg/kg dose pine oil was intraperitoneally injected every next day. While the GSH and total protein were significantly decreased in the Streptozotocin (STZ) group, their levels were protected in PO group. MDA level was significantly increased in STZ group, its level significantly decreased in the PO group. Our results showed that PO has a positive effect on the GSH, total protein, and MDA levels in the brain tissue of diabetic rats. The PO and STZ administrations were affected by levels of some important fatty acids. The decrease in the MDA level and observed protecting effects can be attributed to PO extract, because it contains some important phytochemical constituents. © 2016, Chemical Society of Pakistan. All rights reserved.
Keywords: Brain; Cholesterol; Diabetes; Glutathione; MDA; Pine oil